Candy Soup! a Rugrats Halloween - Wax, Wendy; Marantz, Larissa (New York : Simon Spotlight/Nickelodeon, 2004)
Too sick to go trick-or-treating with the other Rugrats, Kimi is allowed to eat only healthy food on Halloween, but brother Chuckie thinks of a way for her to share their candy.
"Based on the TV series Rugrats created by Arlene Klasky, Gabor Csupo, and Paul Germain as seen on Nickelodeon."
86095
Keywords: Halloween -- Fiction; Sick -- Fiction; Brothers and sisters -- Fiction; Soups -- Fiction